ENDIDIKAN KARAKTER DALAM ISLAM: TINJAUAN ATAS KONSEP AL-GHAZALI - Masithah Masithah (Jurnal Pendidikan Nusantara, 2024)
Character education is an important aspect in the Islamic education system, which aims to form individuals with noble character and high moral awareness. Al-Ghazali, as one of the great thinkers in Islam, made a significant contribution to the concept of character education through the approach of Sufism and Islamic philosophy. This article aims to examine the concept of character education according to Al-Ghazali, by highlighting aspects of methodology, basic principles, and its relevance in the context of modern education. This study uses a qualitative method with a literature analysis approach to Al-Ghazali's works, such as Ihya' Ulumuddin and Ayyuha al-Walad. The results show that character education according to Al-Ghazali centers on purifying the heart (tazkiyat al-nafs), strengthening noble morals (makarim al-akhlaq), and integration between knowledge and charity. This concept is still relevant in building an education system that emphasizes the formation of a balanced personality between intellect and spirituality.